2017
DOI: 10.1186/s12958-017-0236-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fertility stress on endometrial and subendometrial blood flow among infertile women

Abstract: BackgroundTo investigate the effect of fertility stress on endometrial and subendometrial blood flow among infertile women.MethodsThis case–control study was conducted in The First Affiliated Hospital of Zhengzhou University. The fertility problem inventory (FPI) was adopted to evaluate fertility stress. Three-dimensional power Doppler ultrasonography (3D PD-US) was performed during the proliferative phase of the menstrual cycle (days 5–11) to measure endometrial thickness, pattern, endometrial and subendometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…In addition, national and regional registries are attempting to collect data on ART treatments, with some success in Latin America and Africa ( Zegers-Hochschild et al , 2013 ; SARA report, 2014 ; Zegers-Hochschild et al , 2014 ; et al , 2015; et al , 2016). More rigorous data reporting, collection and verification are needed from LMIC to enable a meta-analysis in the future ( Kushnir et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, national and regional registries are attempting to collect data on ART treatments, with some success in Latin America and Africa ( Zegers-Hochschild et al , 2013 ; SARA report, 2014 ; Zegers-Hochschild et al , 2014 ; et al , 2015; et al , 2016). More rigorous data reporting, collection and verification are needed from LMIC to enable a meta-analysis in the future ( Kushnir et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental efforts have previously hinted the in vivo role of G-CSF on spermatogenesis. Accordingly, GC depleting effects by cytotoxic drugs [19,20] or radiation [38] were reversed with G-CSF. We tested r-met-hu G-CSF during pre-puberty, a time window on which GCs expand and differentiate in a divergent way with intense germ stem cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, G-CSF receptor CSF3R has been identified in murine SSCs [19]. Testicular damage from chemotherapy influence the physiological regeneration of male GCs in the testis [20,21], up to a limit imposed by Sertoli cell numbers [20] and G-CSF seems to have a protective role in radiation-induced testicular impairment [21] Currently, there are several types of human recombinant G-CSF (rhG-CSF) commercially available for clinical applications [2224]. The non-glycosylated r-met-hu G-CSF, known as r-met-hu/G-CSF, has been successfully used to stimulate proliferation and maturation of hematopoietic cells [11,25].…”
Section: Introductionmentioning
confidence: 99%
“…( 6 ) Stress can also affect the hypothalamic-pituitary-ovarian axis by reducing hypothalamic gonadotropin-releasing hormone secretion, in turn reducing pituitary secretion of luteinizing hormone and follicle-stimulating hormone, thereby reducing ovarian hormone synthesis and, in some cases, ovulation. ( 7 ) Psychological stress increases the concentration of glucocorticoids and catecholamines ( 8 ) which can excite catecholamines alpha receptors and cause vasoconstriction, thereby reducing uterus blood flow ( 7 ) which may reduce endometrial and sub-endometrial blood flow and thus pregnancy outcomes (both in IVF and non-IVF pregnancy attempts). ( 7 ) In addition, research has shown that psychological stress can trigger embryonic death.…”
Section: Massage and Psychological Stress-induced Infertilitymentioning
confidence: 99%
“…( 7 ) Psychological stress increases the concentration of glucocorticoids and catecholamines ( 8 ) which can excite catecholamines alpha receptors and cause vasoconstriction, thereby reducing uterus blood flow ( 7 ) which may reduce endometrial and sub-endometrial blood flow and thus pregnancy outcomes (both in IVF and non-IVF pregnancy attempts). ( 7 ) In addition, research has shown that psychological stress can trigger embryonic death. ( 9 11 ) The exact mechanism for this loss is unknown, but a decrease in pregnancy-protective cytokines, a reduction in progesterone and prolactin, and elevated glucocorticoids are all thought to contribute to stress-triggered pregnancy loss such as miscarriage.…”
Section: Massage and Psychological Stress-induced Infertilitymentioning
confidence: 99%